Das inscrições da patologização em metamorfoses no mundo da vida: ensaio de psicologia social crítica - Souza Filho, José Alves de (2022)
This thesis is a study about the pathologization processes of the Lifeworld in contemporary society. Thus, we discuss when scientific justifications on the issues and motivations of significant experiences of everyday life take on the contours of identities coherent with the interests of a capitalist society, which selectively determines the meanings of efficiency, functionality, effectiveness and profitability as meanings of life. It is a research affiliated with the work of the identity-metamorphosis-emancipation syntagma of Critical Social Psychology articulated with the social theory of the Lifeworld in the critical theory of society by Jürgen Habermas. Methodologically, we work with the critical operations of Reconstruction. In the presentation, we discussed psychosocial health-illness issues triggered by the COVID-19 pandemic. In the prologue, we present our theoretical-methodological framework and the research problem. In the first study, entitled “Phenomenological Interpellations for Identity Research from the Perspective of Critical Social Psychology”, we discuss the relations on phenomenology for the studies of identity-metamorphosis, based on the themes of the Lifeworld (Lebenswelt) in researches on identity-metamorphosis. metamorphosis. In the second study, “Critique of the pathologization of identities/alterities in the Lifeworld”, we problematize the pathologization of contemporary psychic suffering as a product of the ethical-political minimization of identities/alterities in the contemporary Lifeworld. Finally, in the epilogue, we discuss pathologization as a selective system of sociability on the dispositions of psychosocial elements for the construction of identities, processes operated by identity politics that determine the forms of human recognition in the public sphere as a function of learning behaviors, values and attitudes framed within the discourse of normality.